Identification of candidate microRNA biomarkers of mouse cholangiocyte injury by global miRNAome analysis - Lawrence Howell; Joseph P. Brown; Shiva Seyed Forootan; Ben Francis; Carolyn Jones; Lucia Livoti; Lorenzo Ressel; Emanuele Ricci; Martin Bushell; Chris Goldring (Toxicology and Applied Pharmacology, 2026)

A Pre-registered Meta-analysis Based on Three Empirical Studies Reveals No Association Between Prenatal (Amniotic) Cortisol Exposure and Fluctuating Asymmetry in Human Infants - Will Bushell; Martin Heil; Teresa Ventura; Manuel C. Gomes; Lisa M. Körner; Judith Lawrenz; Nora K. Schaal; Gareth Richards (Evolutionary Biology, 2021)
Developmental instability (DI) reflects an organism’s inability to develop an ideal phenotype when challenged by genetic and environmental insults. DI can be estimated via the proxy measure of fluctuating asymmetry (FA), i.e., the small random deviations from perfect bilateral symmetry observed in the morphology of paired traits. The mechanisms involved in the genesis of FA in human populations are relatively unknown, though animal research indicates that hormonal processes may be involved. As maternal stress during pregnancy is detrimental to various developmental processes, elevated prenatal cortisol may represent a causal factor in the subsequent emergence of an asymmetrical phenotype. The main purpose of this pre-registered meta-analysis based on three empirical studies was to investigate whether mid-trimester amniotic cortisol levels predict subsequent FA in finger lengths of infants from Germany, Portugal, and the UK. No statistically significant relationships were observed, and meta-analytic combination of the effect size estimates yielded a null result. We did, however, detect significant positive correlations between the cortisol present in the amniotic fluid and maternal plasma in the Portuguese cohort, and observed that FA in the German cohort was significantly lower at 70-months than at either 9- or 20-months. Taken together, the current findings run contrary to animal research showing that elevated prenatal corticosterone exposure leads to increased FA. However, this may be because a single cortisol assay obtained via amniocentesis is an inadequate proxy for average gestational exposure, and/or that prenatal cortisol levels at an earlier (i.e., first rather than second trimester) stage of pregnancy is what explains variance in subsequent FA.

The mammalian gene function resource: the international knockout mouse consortium - Allan Bradley; Konstantinos Anastassiadis; Abdelkader Ayadi; James F. Battey; Cindy Bell; Marie-Christine Birling; Joanna Bottomley; Steve D. Brown; Antje Bürger; Carol J. Bult; Wendy Bushell; Francis S. Collins; et al. (Mammalian Genome, 2012)

The impact of vertical resolution upon GCM simulations of marine stratocumulus - A. C. Bushell; G. M. Martin (Climate Dynamics, 1999)